ASSESSING THE EVIDENTIARY POWER: NOTARIZED AUTOPSY REPORTS VERSUS VISUM ET REPERTUM - Marwah Marwah; Anwar Borahima; Ahsan Yunus; Alya Saphira; Santy Kouwagam (Indonesia Private Law Review, 2025)
In cases of murder or suspicious death, an autopsy reports serve as crucial evidence in criminal adjudication. Based on Indonesian criminal procedural law, a Visum et Repertum issued by an authorized forensic doctor is legally recognized as expert evidence for determining the cause, manner, and circumstances of death. In the case examined, both the Visum et Repertum and the testimony of a general practitioner who observed the autopsy process, subsequently legalized by a notary, were submitted as evidence in criminal proceedings. This study examines the normative ambiguity between criminal procedural law and notarial law, particularly regarding the evidentiary status of a general practitioner’s testimony concerning autopsy observations that is subsequently legalized by a notary. This research uses a normative legal analysis, drawing on statutory and conceptual approaches, to analyze the framework of criminal procedural law, regulations governing medical practice, and the juridical limits of notarial authority. The findings confirm that submitting a general practitioner’s testimony on autopsy observations, even when legalized by a notary, does not create a conflict of norms. Instead, it constitutes a misapplication of evidentiary principles. A Visum et Repertum, prepared by a duly authorized forensic physician, possesses definitive evidentiary authority as it is issued within statutory mandate. By contrast, the testimony of a general practitioner, even if notarized, lacks the legal force to constitute valid evidence, as notaries are not authorized to legitimize forensic medical findings. This article clarifies that notarizing autopsy observations does not create normative conflict, but reflects a misapplication of evidentiary authority in criminal procedure.